2021
DOI: 10.3389/fpls.2020.590990
|View full text |Cite
|
Sign up to set email alerts
|

Mini Review: Transport of Hydrophobic Polymers Into the Plant Apoplast

Abstract: The plant apoplast contains the four hydrophobic polymer, lignin, suberin, cutin, and cutan, that are crucial for stress resistance, controlling solute diffusion, and strengthening the cell wall. Some of these polymers are widely used in industry and daily life products, such as all wood-containing goods (lignin) and wine cork (suberin). Despite the importance of these polymers, several aspects of their formation remain unknown. This mini review highlights technical bottlenecks in the current research and summ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 67 publications
0
10
0
Order By: Relevance
“…In addition to the translocation mechanisms mentioned above, lipid-transfer proteins (LTPs), which are small proteins of maximum 10 kDa, can play a role in facilitating the diffusion of hydrophobic molecules through membranes or can assist transmembrane transporters, such as ABCGs [ 61 ]. In more detail, LTPs can diffuse through membranes and present a tunnel-like hydrophobic cavity, which binds lipids or other hydrophobic compounds that are deposited in the apoplast, such as lignins or suberin [ 61 , 62 , 63 ]. However, since it has been shown that members of this family are able to bind isoprenoids (e.g., carotenoids) [ 64 , 65 , 66 ], it cannot be excluded that these proteins might also be involved in the translocation of lipophilic PSMs.…”
Section: General Transport Mechanisms For Psmsmentioning
confidence: 99%
“…In addition to the translocation mechanisms mentioned above, lipid-transfer proteins (LTPs), which are small proteins of maximum 10 kDa, can play a role in facilitating the diffusion of hydrophobic molecules through membranes or can assist transmembrane transporters, such as ABCGs [ 61 ]. In more detail, LTPs can diffuse through membranes and present a tunnel-like hydrophobic cavity, which binds lipids or other hydrophobic compounds that are deposited in the apoplast, such as lignins or suberin [ 61 , 62 , 63 ]. However, since it has been shown that members of this family are able to bind isoprenoids (e.g., carotenoids) [ 64 , 65 , 66 ], it cannot be excluded that these proteins might also be involved in the translocation of lipophilic PSMs.…”
Section: General Transport Mechanisms For Psmsmentioning
confidence: 99%
“…The transfer of suberin monomers, especially aliphatic monomers destined for the SPAD, are reliant in part on half-size ABC transporters and lipid transfer proteins [109]. For example, a rice transporter, RCN1/OsABCG5, is required for root suberization [84], while a pathogen-inducible potato transporter, StABCG1, is involved in the deposition of suberin in tuber skin [25].…”
Section: Atp-binding Cassette (Abc) Transportersmentioning
confidence: 99%
“…Aside from these hypotheses, a denser cytoplasm in swollen root tips could help establish an effective barrier to solutes (Chen et al, 2011), T A B L E 2 Differential expression of genes associated with the suberin, phenylpropanoid, cutin, and cuticular wax biosynthesis Franke et al, 2009;Lee et al, 2009;Lopes et al, 2020;Paul et al, 2006;Rains et al, 2017;Soler et al, 2007;Trenkamp et al, 2004 Benveniste et al, 1998;Höfer et al, 2008;Li et al, 2007;Lopes et al, 2020;Molina et al, 2009;Rains et al, 2017;Soler et al, 2007 Rains et al, 2017;Shanmugarajah et al, 2019;Shiono et al, 2014;Soler et al, 2007;Xin & Herburger, 2020;Yadav et al,…”
Section: Histochemical and Chemical Analysismentioning
confidence: 99%